2021
DOI: 10.1111/jgs.17091
|View full text |Cite
|
Sign up to set email alerts
|

“My backpack is so heavy”: Experiences of Latino caregivers of family with early‐onset Alzheimer's

Abstract: Background/Objectives While it is well‐known that caregiving can have adverse effects on the physical and mental health of informal caregivers and their families, caregivers of those with early‐onset Alzheimer's Disease (EOAD) may have distinct needs. Little is written about the experiences of Latino caregivers of family members with EOAD, especially inherited forms. This study's objective was to explore the experiences and needs of Latino caregivers of persons with EOAD. Methods Five focus group discussions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…research but may also result in more culturally appropriate and effective services. [420][421][422][423][424][425][426][427][428][429][430][431][432] In addition, a greater understanding is needed of how multiple chronic diseases (multimorbidity) intersect with dementia among Black people, indigenous peoples and people of color. 433…”
Section: Race/ethnicity and Dementia Caregivingmentioning
confidence: 99%
See 1 more Smart Citation
“…research but may also result in more culturally appropriate and effective services. [420][421][422][423][424][425][426][427][428][429][430][431][432] In addition, a greater understanding is needed of how multiple chronic diseases (multimorbidity) intersect with dementia among Black people, indigenous peoples and people of color. 433…”
Section: Race/ethnicity and Dementia Caregivingmentioning
confidence: 99%
“…This hinders the progress of all Alzheimer's disease caregiving research, and, by extension, if these individuals continue to lack representation in Alzheimer's research, they will not receive the benefits of prevention, treatment or care innovations 413 . Establishing stronger relationships with existing organizations and resources in Black communities, indigenous communities and communities of color offers the potential of research‐based partnerships that not only enhance representation in Alzheimer's disease research but may also result in more culturally appropriate and effective services 420–432 . In addition, a greater understanding is needed of how multiple chronic diseases (multimorbidity) intersect with dementia among Black people, indigenous peoples and people of color 433 …”
Section: Caregivingmentioning
confidence: 99%
“…Of the 42 studies, two were conducted on members of families with a history of EOAD ( Withers et al, 2019 , 2021 ). In the preclinical stage, two of the studies were conducted on PSEN variant carriers ( Ringman et al, 2004 , 2007a ) and 12 on subjects with a history or carriers of EOAD-associated variants Ringman et al, 2008a , b , 2011 , 2012b , d , e ; Golob et al, 2009 ; Medina et al, 2011 , 2021 ; Braskie et al, 2013 ; Petok et al, 2018 ; Joe et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…After presenting the studies exclusively to PSEN , we categorized those who reported in combination with APP . In Table 5 , we present these articles in three categories: first, articles with PSEN1 and APP ( Ringman et al, 2007b , 2008a , b , 2010 , 2011 , 2012a , b , c , d , e ; Golob et al, 2009 ; Apostolova et al, 2011 ; Braskie et al, 2012 , 2013 ; Lee et al, 2013 ; Joe et al, 2019 ; Medina et al, 2021 ; Singer et al, 2021 ); second, articles with PSEN1, PSEN2 , and APP variants ( Albrecht et al, 2009 ; Medina et al, 2011 ; Ringman et al, 2016 ; Petok et al, 2018 ), and finally, those articles who reported families with a history of EOAD ( Withers et al, 2019 ) and another with A431E PSEN1 and an unknown mutation ( Withers et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation